2010
DOI: 10.1371/journal.pone.0009299
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Phenotypically Converts and Selectively Inhibits Metastatic Cells in Mice

Abstract: Skeletal muscle is rarely a site of malignant metastasis; the molecular and cellular basis for this rarity is not understood. We report that myogenic cells exert pronounced effects upon co-culture with metastatic melanoma (B16-F10) or carcinoma (LLC1) cells including conversion to the myogenic lineage in vitro and in vivo, as well as inhibition of melanin production in melanoma cells coupled with cytotoxic and cytostatic effects. No effect is seen with non-tumorigenic cells. Tumor suppression assays reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…As we found striking differences between cancer cell extravasation within BMi and muscle-mimicking microenvironments, we asked which factors secreted by muscle might be responsible. It is reported that the skeletal muscle microenvironment reduces cancer cell tumorigenicity and elicits paracrine-mediated cytotoxic and cytostatic responses from metastatic cancer cells (30). In particular, several studies identified the A 3 adenosine receptor (A 3 AR), which is expressed by multiple cancer cell types (31), as key in the antimetastatic and protective effect of skeletal muscle cells (32).…”
Section: Generation Of Functional 3d Microvascular Network Within a Bmimentioning
confidence: 99%
“…As we found striking differences between cancer cell extravasation within BMi and muscle-mimicking microenvironments, we asked which factors secreted by muscle might be responsible. It is reported that the skeletal muscle microenvironment reduces cancer cell tumorigenicity and elicits paracrine-mediated cytotoxic and cytostatic responses from metastatic cancer cells (30). In particular, several studies identified the A 3 adenosine receptor (A 3 AR), which is expressed by multiple cancer cell types (31), as key in the antimetastatic and protective effect of skeletal muscle cells (32).…”
Section: Generation Of Functional 3d Microvascular Network Within a Bmimentioning
confidence: 99%
“…4A, B). As pericytes differentiated into myofibers [11,13], we exposed them to myogenic differentiation conditions and examined the expression of myogenin, a marker of cell differentiation [35], and MHC, a myotube marker [36]. We found that only type-2 pericytes differentiated into the muscle lineage (Fig.…”
Section: Type-2 But Not Type-1 Pericytes Differentiate Into Muscle Cementioning
confidence: 91%
“…Metastatic tumor cells, after extravasation, at a metastatic site, find themselves in foreign microenvironments. Tumor cells are known to be very sensitive to changes in microenvironmental conditions, which can lead to alterations of fundamental properties of these cells [64,65]. Experimental evidence in melanoma suggests that induction of apoptosis by Fas/Fas-ligand at metastatic sites is an important negative regulator of metastasis [66].…”
Section: Dormancy In Metastatic Melanomamentioning
confidence: 99%